122. Does vertebral body tethering cause disc and facet joint degeneration? An MRI study with minimum two years of follow-up - Yucekul, Altug; Akpunarli, Burcu; Durbas, Atahan; Zulemyan, Tais; Havlucu, Irem; Ergene, Gokhan; Snay, Sahin; Dikmen, Pinar Yalinay; Balci, Sule Turgut; Karaarslan, Ercan; Yavuz, Yasemin; Yilgor, Caglar; et al. (The spine journal, 2021)
Disc health after various growth modulation techniques have been assessed in animal models, and tethering was claimed to prevent degeneration due to its less rigid nature compared to other growth-friendly techniques. Yet, the results of animal studies wherein tethering is applied on healthy spines to create a deformity cannot be extrapolated to humans, in which tethering is used for deformity correction. As biomechanical properties are different, effects of vertebral body tethering (VBT) surgery on discs and facet joints in clinical series are not precisely acknowledged. There are concerns that VBT surgery may cause degeneration at both intermediate and adjacent levels. Our aim was to investigate the integrity of discs and facet joints that are subject to compressive forces and relative stabilization during growth modulation. Retrospective analysis of a prospectively collected data. This study included 25 (23F, 2M) consecutive adolescent idiopathic scoliosis (AIS) patients with a mean follow-up of 29 (24-62) months who underwent thoracoscopic VBT surgery between 2014 to 2017 were included. Disc and facet joint degeneration scores on MRI. Demographic, perioperative and radiographic data were collected. Overcorrection, mechanical and pulmonary complications, and reoperations were recorded. MRIs taken before surgery and at a minimum of 2 years of follow-up were evaluated for degeneration at the intermediate and adjacent segment intervertebral discs and facet joints by a blinded senior radiologist and compared. Discs were assessed using Pfirrmann grade. Facet joint degeneration was graded on a scale of 0-3. Changes from preop to follow-up MRIs were analyzed using McNemar's Test and Related Samples Marginal Homogeneity Test. The mean age at surgery was 12.2 (10–14) years and median Sanders stage was 3 (1-7). A mean of 7.7±1.1 (6-11) levels were tethered. Preoperative mean height of 155.3 (130-178) cm was increased to 163.4 (149-187) cm at latest follow-up. The mean preoperative MT curve magnitude of 46°±7.7° was corrected to 23.3°±5.9° at first erect, which was modulated to 12°±11.5° during follow-up. There was 1 (4%) broken tether, 5 (20%) overcorrected curves, 3 (12%) implant-related complications and 1 (4%) reoperation for a thoracoscopic tether release before the follow-up MRI was obtained. A total of 217 levels of discs and bilateral facet joints, were evaluated in the preoperative and follow-up MRI images. Analyses of disc and facet joint scores revealed no significant differences between patients. One case (4%) with an increase in disc scores already had multilevel moderate degeneration preoperatively, while another case (4%) displayed a single-level new-onset grade-2 bilateral facet degeneration. This study reports MRI findings of 25 rapid and steady growing adolescents (Sanders 2-7) who had undergone thoracoscopic VBT surgery. At an average of 29 months (24-62) after growth modulation with VBT surgery, radiographic degenerative findings were not present in 97.7% of the intermediate and adjacent discs and 99.3% of the facet joints. Studies with longer follow-up are warranted to further analyze the effects of relative stabilization and altered biomechanical loads. This abstract does not discuss or include any applicable devices or drugs.